Digital Fortress - Brown, Dan (London Corgi Books, 2004)
A new master of smart thrills' People magazineSusan Fletcher has been summoned to the one of the world's most secretive organisations, the National Security Agency. Their unbeatable code-breaking machine has been hacked.Susan is supposed to be able to help.Can she protect her country from the most deadly of enemies?
Keywords: Computer security -- Cryptographers -- Intelligence officers